PARENT'S ROLE PREVENTING EARLY MARRIAGE - Suci Larasati; Tetti Solehati; Hesti Platini (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Background: Early marriage has many negative impacts; therefore, parents needed an effort to prevent early marriage. Purpose: To describe the role of parents in preventing early marriage. Method: quantitative descriptive, Accidental sampling technique, with a sample size of 95. The study was conducted in May 2019. The research instrument was a questionnaire on the Role of Parents in Preventing Early Marriage, modified from Novianti (2017), contained 30 questions, with a validity score of 0.3785 and alpha cronbach 0.707. Data analysis using frequency distribution. This research had been registered to the ethics committee with the ethics number of 535/UN6.KEP/EC/2019. Result: 56 people (59%) parents done their role excellent in preventing early marriage. Of the five roles of parents, the role of parents was an educator 64 (67%), role models and friends 46 (48%), counselor 40 (53%), and 60 (63%) as a communicator. Conclusion: the role of parents in preventing early marriage was categorized as either the role of educator, communicator and counselor, while the role of parents as friends and role models was said to be wrong. Suggestion: education about early marriage to the community and adolescents to reduce or minimize early marriage incidence Keywords: Prevention, Early Marriage, Role of Parents